Recombinant expression of an oriental river prawn anti-lipopolysaccharide factor gene in Pichia pastoris and its characteristic analysis. Issue 98 (March 2020) - Tang, Ting; Liu, Jinlan; Li, Shuangshuang; Li, Hongquan; Liu, Fengsong
Abstract: Anti-lipopolysaccharide factors (ALFs), as main host-defense molecules of crustaceans, form a unique family of antimicrobial peptides (AMPs). MnALF4 is one isoform of ALFs isolated from the freshwater prawn Macrobrachium nipponense . In the present study, MnALF4 gene was successfully expressed in the yeast Pichia pastoris and the recombinant MnALF4 protein exhibited efficient and broad-spectrum antimicrobial activities against both Gram-positive bacteria and Gram-negative bacteria in vitro . When prawns were injected with rMnALF4 before bacterial challenge with E. coli, the recombinant protein effectively promote the elimination of bacteria by the host. It manifested that rMnALF4 could effectively kill the invading bacteria in vivo . Treatment with rMnALF4 led to remarkable changes in bacterial morphology, such as spheroidization, oversized bacteria, and cell lysis. In addition, rMnALF4 showed weak hemolysis activity to the rabbit red blood cells. Our work suggests that MnALF4 plays an important role in Macrobrachium immunity and is worthy of further investigation as a potential antibacterial agent with high efficacy against bacterial infection and low toxicity to host cells. Highlights: Antimicrobial peptide MnALF4 was recombinantly expressed in Pichia pastoris. The rMnALF4 showed broad-spectrum antibacterial activity and weak hemolysis activity. Treatment with rMnALF4 led to remarkable changes in bacterial morphology.